Sanger Sequencing of Borrelia burgdorferi flaB Paralogs Detected Spirochetemia at the Early Localized Stage of Lyme Disease - Sin Hang Lee (Frontiers in Bioscience-Scholar, 2025)
Background: The general assumption that spirochetemia does not occur at the early localized stage of Lyme disease is due to a lack of sensitive and specific methods for molecular diagnosis. Methods: During a Lyme disease season in 2023, the platelet-rich plasma specimens of 145 people residing in Lyme disease-endemic areas in the United States were immediately separated from the blood cells following venous blood collection to prevent the spirochetes, if any, from invading the lymphocytes in the test tube. The entire DNA content was extracted from the platelet pellet and used for split sample polymerase chain reaction (PCR) amplification; Sanger sequencing was performed on the nested PCR products to detect the Borrelia burgdorferi flaB and 16S rRNA genes. Results: In 98 of the people who were clinically suspected of having early localized Lyme disease irrespective of the presence or absence of a skin lesion, 33 of their blood specimens (33.7%) were positive for Borrelia burgdorferi (B. burgdorferi), including 17 positive for flaB gene only, 15 positive for both the flaB and 16S rRNA genes, and one positive for 16S rRNA gene only. Eight (17.0%) of the 47 asymptomatic resident controls were positive for flaB PCR only. Conclusions: The flaB gene is a more sensitive chromosomal target than the 16S rRNA gene for molecular detection of one to three B. burgdorferi cells due to spirochetes gaining or retaining flaB paralogs at the early localized stage of Lyme disease.